Pathways to STEM identity: high school students' perceptions in Qatar - Sellami, Abdellatif; Santhosh, Malavika E.; Michaleczek, Igor Jacky Dimitri (Frontiers in Education, 2025)
IntroductionThis study delves into the intricate relationship between various constructs of student identity formation, which helps comprehend their subsequent impact on students' interest and persistence in Science, Technology, Engineering, and Mathematics (STEM) fields. Understanding how disciplinary identities contribute to the development of a holistic STEM identity is critical for shaping effective educational strategies.MethodsUtilizing a survey-based quantitative approach, this research encompasses data from 1,428 high school students. The study examined the influence of disciplinary identities in Mathematics, Science, and IT on the overall STEM identity.ResultsThe principal findings underscore that students' identities in specific disciplines-Mathematics identity (β = 0.55, p < 0.001), Science identity (β = 0.12, p < 0.001), and IT identity (β = 0.36, p < 0.001)-positively influence their overall STEM identity. Among these, the Mathematics identity exhibited the most substantial positive relationship. Additionally, the constructs associated with each disciplinary identity, particularly “recognition” and “sense of belonging,” demonstrated the strongest correlations within STEM subjects.DiscussionThese insights are pivotal for policymakers and educators aiming to cultivate a robust STEM identity among the younger generation. By fostering recognition and a sense of belonging within STEM subjects, these findings pave the way for more inclusive and effective strategies in STEM education.